Emotion dysregulation as a mechanism linking peer victimization to internalizing symptoms in adolescents - McLaughlin, Katie A; Hatzenbuehler, Mark L; Hilt, Lori M (Journal of consulting and clinical psychology, 2009)
Peer victimization experiences represent developmentally salient stressors among adolescents and are associated with the development of internalizing symptoms. However, the mechanisms linking peer victimization to adolescent psychopathology remain inadequately understood. This study examined emotion dysregulation as a mechanism linking peer stress to changes in internalizing symptoms among adolescents in a longitudinal design. Peer victimization was assessed with the Revised Peer Experiences Questionnaire (M. J. Prinstein, J. Boergers, & E. M. Vernberg, 2001) in a large (N = 1,065), racially diverse (86.6% non-White) sample of adolescents 11-14 years of age. Emotion dysregulation and symptoms of depression and anxiety were also assessed. Structural equation modeling was used to create a latent construct of emotion dysregulation from measures of discrete emotion processes and of peer victimization and internalizing symptoms. Peer victimization was associated with increased emotion dysregulation over a 4-month period. Increases in emotion dysregulation mediated the relationship between relational and reputational, but not overt, victimization and changes in internalizing symptoms over a 7-month period. Evidence for a reciprocal relationship between internalizing symptoms and relational victimization was found, but emotion dysregulation did not mediate this relationship. The implications for preventive interventions are discussed.